Allergy Methods and Protocols - Jones, Meinir G.; Lympany, Penny; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2008)
In recent years, allergy research has focused on the causes and mechanisms of allergy. In parallel, there is also an impetus to try to understand mechanisms of natural tolerance and immunotherapy where allergy is being dampened. In Allergy: Methods and Protocols a groundbreaking new title from the Methods in Molecular Medicine series, leaders in the field provide assistance for researchers to gain insight into the molecular mechanisms involved in allergy by featuring an array of protocols. These cover a range of disciplines including allergy, immunology, cell biology and histology and include methods to investigate the cellular response to allergens, cytokine profile, MHC restriction, T regulatory cells. Techniques discussed include; B and T cell epitope mapping, characterization of allergens, conjugation of haptens, preparation of monoclonal antibodies, collection and sampling of airborne allergens, IgG antibodies and facilitated antigen blocking assays, identification and purification of mast cells and in situ hybridisation. Allergy: Methods and Protocols will be a remarkably useful bench tool for anyone embarking in or continuing with their research in allergy.
Understanding of the Molecular Mechanisms of Allergy -- T Cell $1 (BPrimary Culture from Peripheral Blood -- Production of T-Cell Lines -- Production of Human T-Cell Clones -- Mapping of Human T-Cell Epitopes of Allergens -- Determining MHC Restriction of T-cell Responses -- Short-Term Culture of CD8 Cells and Intracellular Cytokine Staining -- Isolation, Flow Cytometric Analysis, and Suppression Assay of CD4+ CD25+ T-Regulatory Cells -- Monocyte-Derived Dendritic Cells as Antigen-Presenting Cells in T-Cell Proliferation and Cytokine Production -- Ultrasensitive ELISA for Measurement of Human Cytokine Responses in Primary Culture -- Quantification of Human Chemokine Production in TLR-Stimulated and Antigen-Specific Recall Responses -- Standardization of Allergen Extracts -- Immunoelectrophoresis for the Characterization of Allergen Extracts -- Conjugation of Haptens -- Monoclonal Antibodies -- Purification of Antibodies -- Collection of Air Samples to Quantify Exposure to Airborne Allergens -- Assay of Air Sample Eluates -- The Halogen Assay - A New Technique for Measuring Airborne Allergen -- Measurement of Specific IgG Anti-Fel d 1 Antibodies -- The Facilitated Antigen Binding (FAB) Assay - A Protocol to Measure Allergen-Specific Inhibitory Antibody Activity -- Microscopic Identification and Purity Determination of Pollen Grains -- Biopanning for the Characterization of Allergen Mimotopes -- Identification of Mast Cells and Mast Cell Subpopulations -- Purification and Characterization of Mast Cell Tryptase and Chymase from Human Tissues -- Experimental Activation of Mast Cells and Their Pharmacological Modulation -- In situ Hybridization.s
Keywords: Medicine; Immunology; Laboratory medicine; Biomedicine; Immunology; Laboratory Medicine; Electronic books